Satellite-observed precipitation and total column water vapor - Johnson, Sara E. A.; Ye, Hengchun; Fetzer, Eric J.; Li, Jingjing (Frontiers in Environmental Science, 2024)
This study explores the relationship between water vapor and rainfall intensities over three tropical lands (Amazon Basin, Sahel, southern South America) and three tropical ocean regions (Atlantic Ocean, Indian Ocean, Niño 4). We utilized daily total column water vapor (TCWV) data from the Atmospheric Infrared Sounder (AIRS) and daily precipitation records from the Tropical Rainfall Measurement Mission (TRMM) Multi-satellite Precipitation. Over tropical land, precipitation shows higher sensitivity to changes in water vapor, with a well-sorted pattern of an increased occurrence of higher daily precipitation as TCWV increases. Precipitation intensity over the Sahel, in particular, is extremely responsive to TCWV change. Over tropical oceans, the precipitation intensity is less sensitive to water vapor, particularly in the Indian Ocean and Niño 4 where precipitation intensities above the 40th percentile are no longer responding to the increasing TCWV. Quantifying water vapor and precipitation intensity aids in forecasting the occurrence of precipitation between tropical land and oceans.